Padrões de duração de seis vogais do inglês produzidas por alunos brasileiros (Duration patterns of six english vowels produced by brazilian learners) - Lima Jr., Ronaldo (2014)
This paper presents the main characteristics in durational patterns of the pairs of vowels [i: I] [E æ] [u: U] as produced by Brazilian learners who started learning English as a Foreign Language at different ages. The students were in the last semester of their EFL courses and have acquired English exclusively in Brazilian classrooms.KEYWORDS: Second Language Acquisition. Acoustic Phonetics. Phonology. English as a Foreign Language. Vowels.